2016
DOI: 10.2147/ott.s95490
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of hypoxia-inducible factor-1 alpha expression in osteosarcoma: a meta-analysis

Abstract: BackgroundHypoxia-inducible factor-1α (HIF-1α) plays an important role in tumor progression and metastasis. A number of studies have investigated the association of HIF-1α with prognosis and clinicopathological characteristics of osteosarcoma but yielded inconsistent results.MethodSystematic computerized searches were performed in PubMed, Embase, and Web of Science databases for relevant original articles. The pooled hazard ratios (HRs) and odds ratios (ORs) with corresponding confidence intervals (CIs) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…HIF-1α is highly expressed in hypoxic conditions and is recognized as a predictor of tumor diagnosis and recrudescence, monitor of invasion and metastasis, and marker of malignant grades in OS [ 38 ]. However, it has also been well demonstrated that HIF-1α is expressed in normal and malignant bone cell lines during normoxia, and is especially high in OS cells [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is highly expressed in hypoxic conditions and is recognized as a predictor of tumor diagnosis and recrudescence, monitor of invasion and metastasis, and marker of malignant grades in OS [ 38 ]. However, it has also been well demonstrated that HIF-1α is expressed in normal and malignant bone cell lines during normoxia, and is especially high in OS cells [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past 20 years, there were no further improvements in osteosarcoma survival. To explain this lack of progress, many studies were performed to investigate factors effecting the progression and metastasis of osteosarcoma, such as levels of C-reactive protein and expression of hypoxia-inducible factor-1 alpha [ 25 , 26 ]. There are several studies which have assessed the association between pathological fracture and prognosis in patients with osteosarcoma; however, the results were inconclusive because of the limited sample of single-study.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of HIF-1α suppresses OS cell growth by inducing apoptosis [59], and the HIF-1α/CXCR4 pathways contribute to metastasis in human OS cells [60]. A recent meta-analysis has suggested that overexpression of HIF-1α is a predictive factor for poor outcomes in OS and could serve as a promising prognostic biomarker to predict the outcome of OS patients [61,62].…”
Section: Hypoxiamentioning
confidence: 99%